2012
DOI: 10.1073/pnas.1210688109
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the human MTERF4–NSUN4 protein complex that regulates mitochondrial ribosome biogenesis

Abstract: Proteins crucial for the respiratory chain are translated by the mitochondrial ribosome. Mitochondrial ribosome biogenesis is therefore critical for oxidative phosphorylation capacity and disturbances are known to cause human disease. This complex process is evolutionary conserved and involves several RNA processing and modification steps required for correct ribosomal RNA maturation. We recently showed that a member of the mitochondrial transcription termination factor (MTERF) family of proteins, MTERF4, recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
104
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(113 citation statements)
references
References 31 publications
9
104
0
Order By: Relevance
“…At this point, we cannot be certain that our recombinant RNMTL1 or MRM1 proteins folded correctly when expressed in bacteria. If any of these proteins require additional factors to stabilize them, as seems to be the case for NSUN4-MTERF4 (19,36,37), these partners have not yet been identified. Because none of the mammalian mitochondrial RNA methyltransferase members we have expressed have robust RNA methyltransferase activity, it is also possible FIGURE 9.…”
Section: Resultsmentioning
confidence: 99%
“…At this point, we cannot be certain that our recombinant RNMTL1 or MRM1 proteins folded correctly when expressed in bacteria. If any of these proteins require additional factors to stabilize them, as seems to be the case for NSUN4-MTERF4 (19,36,37), these partners have not yet been identified. Because none of the mammalian mitochondrial RNA methyltransferase members we have expressed have robust RNA methyltransferase activity, it is also possible FIGURE 9.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that, compared with natural PPR proteins, hydrophobic interactions organizing the overall PPR scaffold are shielded from the solvent by salt bridges between residues at position 17, 27 and 15, 18, 25. This is reminiscent of the binding between NSUN4 and MTERF1 proteins, where salt bridges also flank hydrophobic interactions to provide a very stable interaction interface 34 . In addition, consensus design enabled core structural characteristics of PPRs to be elucidated without interference from the idiosyncratic features present in individual natural proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that mammalian mTERF1, mTERF3, and mTERF4 share a common fold and are structurally similar to each other, even though mTERF3 was crystallized in the absence of its substrate (Spåhr et al, 2010) and mTERF4 in complex with another protein (Spåhr et al, 2012), supports the conclusion that mTERF proteins have evolved to bind nucleic acids (Byrnes and Garcia-Diaz, 2011). However, it is becoming increasingly clear that the nucleic acid need not necessarily be doublestranded DNA (dsDNA); RNAs can also serve as targets of mTERFs.…”
mentioning
confidence: 90%